Team-based care intervention: views and perspectives from patients and healthcare professionals. (30th September 2020) - Pais, B; Wuerzner, G; Chiolero, A; Schaller, P; Cloutier, L; Paradis, G; Burnier, M; Santschi, V
Abstract: Background: Blood pressure (BP) control is poor in European countries. Team-based care (TBC) intervention involving different healthcare professionals has the potential to improve BP control. Within a patient-centered approach, we evaluated patients' and healthcare professionals' opinion about a TBC intervention involving nurses, pharmacists, and physicians (MD). Methods: As part of the TBC study, a pragmatic randomized controlled study to evaluate the impact of a TBC interprofessional intervention on BP control, we collected opinion of patients and team-based members (nurses, community pharmacists, and MD) at the end of study period using specific questionnaires. A mean TBC-satisfaction score was computed, assessing various aspects of the intervention, and ranged from 0 to 60, where a higher score represents a greater satisfaction. Results: All patients (100%), pharmacists (100%), MD (92%) and nurses (80%) were satisfied with TBC intervention. Most patients considered that TBC can help improving BP control (92%), drug intake (71%), and lifestyle habits (84%). Furthermore, patients reported that TBC improved their relationship with nurses (66%), pharmacists (55%), and MD (50%). Patients also reported that their discussion with nurses (95%) and pharmacists (89%) helped improve medication intake. Healthcare professionals considered that TBC improve the quality of care (91%) and an added value for the management of chronic disease (79%). Mean TBC-satisfaction score was higher among MD [42 (SD: 9)] and pharmacists [45 (SD: 6)] compared with nurses [36 (SD: 9)]. Conclusions: Overall, patients and healthcare professionals were highly satisfied regarding TBC engaging different healthcare professionals in a primary care setting. Key messages: TBC intervention seem to be well appreciated by patients and healthcare professionals. Favourable patients' and healthcare professionals' perspectives will help implementing TBC intervention.